Subterranean Waters Described in Carniolan Letters Mailed to A. Kircher (* 1601; †1680) - Stanislav Južnič (Acta Carsologica, 2007)
Kircher’s letters connected with the area of today’s Slovenia were analyzed. His Jesuit informer Wilpenhoffer’s reports on the Cerknica Lake and Idrija Mine were put forward. He also helped distribution of Kircher’s books among Auerspergs and other Ljubljana nobles. Janez Vajkard Auersperg’s letters as an example of high nobility correspondent patronage were put at the limelight in connection with Janez and his admirer Valvasor’s own research of the Postojna Cave flora and fauna.